Users’ Satisfaction with Domestic Water Supply in Nepal – A Study in Lekhnath Small Town Water Supply and Sanitation Project - Timilsena, Narayan (Technical Journal, 2020)
Water Supply and Sanitation has been a priority of Government of Nepal. Various types of urban and rural water supply and sanitation projects are now being implemented within the Government, private and NGO sectors. The normal practice of measurement of satisfaction by service providers is to measure consumers’ satisfaction on past performance. The survey design could vary from survey questions to unstructured interviews and everything in between using comparative and non-comparative scales. In comparative scaling, the respondents are asked to compare one product against the other while non-comparative scaling is used to evaluate a single product. In this study, Likert Scales is used in this study for measurement of customer satisfaction on water supply. The higher level of satisfaction with water supply is expected to be positively related to several factors such as satisfaction with water quality, and other parameters such as hours and timings of water supply, tap pressure, quantity of water supplied, responsiveness and communication of management and water tariff. The respondents’ level of satisfaction indicates that about 41 percent of respondents were neutral, they were neither satisfied nor dissatisfied with water services, while about 36 percent of respondents were satisfied with water services. The satisfaction scale of overall satisfaction with water services was 3.29 while 1.0 indicates strongly not satisfied while 5.0 indicate strongly satisfied. The various aspects that influence satisfaction among users which include hours and timings of water supply, tap pressure, quantity of water supplied, responsiveness and communication of management and water tariff as well as redresses of customer complaints have been examined. This study focused on the users’ satisfaction of Lekhnath small town water supply and sanitation project and the study was undertaken to analyze the current users’ satisfaction of the Lekhnath small town water supply and sanitation project. The result showed that the satisfaction level of users’ is above neutral but these were not in satisfying level. The characteristics/aspects of the service that contributed to users’ satisfaction including hours and timing, pressure, quantity and quality of water while there was slightly less satisfaction with regard to complaints about water supply.